Childhood Maltreatment Is Associated with Adult Psychopathology through Decreased Dispositional Mindfulness. Issue 10 (26th November 2022) - Fitzgerald, Michael
ABSTRACT: Childhood maltreatment has been widely associated with psychopathology in adulthood. Emerging research suggests that dispositional mindfulness may be a pathway linking maltreatment to psychopathology; however, research has almost exclusively investigated depression as the outcome with little inquiry into other, comorbid forms of psychopathology. The current study assesses dispositional mindfulness as a pathway linking maltreatment to depression, anxiety, dissociation, sleep disturbances, sexual problems, and post-traumatic stress disorder symptoms. A cross-sectional sample of 177 young adults (49.2% White; 92% female) enrolled in college completed an online questionnaire assessing childhood maltreatment, mindfulness, and varying forms of adult psychopathology. Using structural equation modeling, the indirect effects from childhood maltreatment to adult psychopathology were estimated while controlling for sociodemographic characteristics. Childhood maltreatment was negatively associated with dispositional mindfulness which, in turn, was negatively associated with depression, anxiety, dissociation, sleep disturbances, sexual problems, and post-traumatic stress disorder symptoms. Childhood maltreatment was directly associated with only sexual problems. The bootstrapped indirect effects were significant to each of the adult psychopathology outcomes. Childhood maltreatment was negatively associated with dispositional mindfulness, and, in turn, the lower levels of dispositional mindfulness were associated with higher levels of depression, anxiety, dissociation, sleep disturbances, sexual problems, and post-traumatic stress disorder symptoms. Mindfulness-based interventions aimed at increasing adult's dispositional mindfulness, such as meditation, may be particularly effective for clinicians working with young adults.